Water budgeting in conservation agriculture-based sub-surface drip irrigation in tropical maize using HYDRUS-2D in South Asia - Patra, Kiranmoy; Parihar, Chiter Mal; Nayak, Harisankar; Rana, Biswajit; Singh, Vinod K; Jat, Shankar Lal; Panwar, Sanjeev; Prihar, Muli D; Singh, Love Kumar; Sidhu, Harminder S.; Gerard, Bruno G.; Jat, Mangi Lal (Springer, 2021)
In water scarce regions of South Asia, diversification of rice with maize is being advocated towards sustainability of cereal-based cropping systems. Adoption of innovative agronomic management practices, i.e., conservation agriculture (CA) and sub-surface drip irrigation (SSDI) are considered as key strategies for much needed interventions to address the challenges of water scarcity under projected climate change. Benefits from CA and SSDI concerning water economy are well-established, however, information about their complementarity and water budgeting in cereal-based systems are lacking. A field study was conducted with process-based model (HYDRUS-2D) to understand water transport, root water uptake and components of soil water balance in maize grown in rotation with wheat after five years of continuous adoption of conservation agriculture. In this study, altogether eight treatments comprising of 6 CA+ treatments (CA coupled with SSDI); permanent beds using sub-surface drip (PB-SSD) with (WR) and without (WOR) crop residue at different N rates, 0, 120 and 150 kg N ha−1 were compared with CA (PB using furrow irrigation-FI with crop residue-120 kg N ha−1) and conventional tillage practices (CT) (CT using FI without crop residue-120 kg N ha−1). Results showed that the model could simulate the daily changes in profile soil water content with reasonable accuracy in all the treatments. Simulated soil water balance indicated higher cumulative root water uptake (CRWU), lower cumulative evaporation (CE) and higher soil water retention in CA+ (PB-SSD+ crop residue at 150 and 120 kg N ha−1) than CA and CT plots. Hydrus-2D model efficiency > 0, RMSE between 0.009–0.026 and R2 value between 0.80–0.92 at P < 0.01 indicates that the model is performing efficiently. The mean evaporation from CA+ treatments was 10 and 36% less than CA and CT treatments, respectively. On average, CRWU under CA+ treatments were 14–48% higher than FI treatments. The mean cumulative deep drainage in CA+ plots was 80–100 mm less than CA and CT plots. In CA+ based plots significantly higher biomass production and radiation use efficiency were observed with reduced water use than CA and CT. Therefore, the study justifies the water-saving nature of CA+, while maintaining higher productivity and meeting the transpiration demand of crops and halting unnecessary evaporation and deep drainage losses.